Estudio de prefactibilidad para la instalación de una planta de producción de crema de ají (Capsicum frutescens) de cocona (Solanum sessiliflorum) - Beraun Colan, Diana Isabel (2022)
The aim of this research work is evaluate feasibility for the installation of a plant producing cocona chilli sauce which market is located on Lima Metropolitana. Initially, the research details the objectives, hypotheses, scope, justification of the topic, referential and theoretical framework which pretends to explain widely details about manufacturing process and terms related to the topic. Throughout the second chapter, the product description will be given in the three levels (basic, real and increased) and product basic features. Furthermore, the industrial sector analysis and the business model adopted by the product. From previous analysis and market study, the demand of the project is being determinated. In addition to this, the research includes the offer analysis and the determination of marketing and distribution policies. In the following chapters, the study encompass the location of the plant, plant size, project engineering, organization and management, and economic, financial and social evaluation. Finally, conclusions will be presented from developed analysis throughout the project and recommendations to validate the hypothesis formulated initially.